Garage from the makers of Adam & Paul - Shortt, Pat 1966-; Duff, Anne-Marie 1970-; Ryan, Conor J.; O'Halloran, Mark ca. 20. Jh (Element Pictures, 2008)
Regarded by his neighbours as a harmless misfit, eliciting idle kindness, benign tolerance and occasional abuse, Josie (Irish comedy legend Pat Shortt) has spent all his adult life as the caretaker of a crumbling petrol station on the outskirts of a small countryside town. He is limited, lonely, yet relentlessly optimistic and, in his own peculiar way, happy. But then, over the course of a summer, Josie's world shifts. Striking up a friendship with a new teenage co-worker (Conor Ryan), suddenly the lonely adult is drinking cans at the railway tracks with the local kids, and confronting his long-buried feelings for local woman Caramel (Anne-Marie Duff: Notes on a Scandal, The Magdelene Sisters). When one thoughtless moment threatens his new friendship and confidence, events spiral and Josie's life is changed forever
Original: Irland 2007
Keywords: Feature films; Service stations / Ireland / Employees / Drama; Marginality, Social / Ireland / Drama; Male friendship / Drama; Video recordings; DVD-Video discs; Video recordings for the hearing impaired; Male friendship; Marginality, Social; Ireland; Dark comedy films; Drama; Fiction films; Motion pictures / Ireland; DVD-Video